Is there any prognostic significance in pleural involvement and/or effusion (Ple-I/E) in patients with ALK-positive NSCLC? - Kılıçkap, Saadettin; Buğdaycı Basal, Fatma; Demirkazık, Ahmet; Gürsoy, Pınar; Demirci, Ufuk; Erman, Mustafa; Yumuk, Fulden; Çay Şenler, Filiz; Çakar, Burcu; Çiçin, İrfan; Öztürk, Akın; Coşkun, Hasan Şenol; et al. (Oxford University Press, 2019)
Background: ALK mutation occurs in approximately 3-5% of patients with NSCLC. At the baseline, Ple-I/E are more frequent in ALK? patients with NSCLC. In the study, we aimed to evaluate characteristics of ALK?patients who have Ple-I/E. Methods: In this multicenter study, patients with ALK? NSCLC who have Ple-I/E were retrospectively analyzed. Clinical and demographic characteristics of the disease, response rates, median PFS and OS were evaluated in 362 ALK?patients with NSCLC. Results: Of the patients, 198 (54.7%) were male. The median age at the time of diagnosis was 54 (21-85) years. The median age was higher in male (57 vs 52 years; p¼0.011). The most common histology was adenocarcinoma (100%). At the baseline, 57 (15.7%) patients had Ple-I/E. The median age of patients with Ple-I/E was similar to patients without Ple-I/E (53 vs 55 years; p¼0.541). The rate of smokers was 43.4% (n¼157) in the patients. There was no association between Ple-I/E and gender, lung metastasis and distant LAP metastasis. Pleural involvement was higher in non-smokers than smokers (19.4% vs 13.4%; p¼0.077), but not statistically significant. The frequencies of liver, brain and bone metastasis were a significant higher in ALK?patients with Ple-I/E compared to those with non-metastatasis (respectively 18.2% vs 4.8%, p¼0.008; 19.1% vs 4.8%, p¼0.002; 20.6% vs 8.9%, p¼0.003). The median PFS was longer in ALK? patients who have Ple-I/E 18.7 vs 10.6 months, p¼0.017). The 1-, 2- and 3-year PFS were 59%, 36%, and 24% in patients with Ple-I/E and 47%, 24%, and 8% in patients with non-involvement. Similarly, the median OS was longer in ALK?patients who have pleural involvement/infusion 44.6 vs 22.6 months, p¼0.051). The 1-, 2- and 3- year OS were 78%, 67%, and 57% in patients with Ple-I/E and 66%, 48%, and 34% in patients with non-involvement. Conclusions: Brain, liver and bone metastases are lower in ALK?patients with Ple-I/E. Presentation with Ple-I/E in patients with ALK? NSCLC is associated with longer overall and progression-free survival. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.
Conference Conference: 44th Congress of the European-Society-for-Medical-Oncology (ESMO) Location: Barcelona, SPAIN Date: SEP 27-OCT 01, 2019 Sponsor(s):European Soc Med Oncol; Japanese Soc Med Oncol
Keywords: ALK-Positive; Effusion; Prognostic Significance